Ziarah : antara Fenomena Mistik dan Komunikasi Spritual - Zaura Sylviana (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This article discusses the communication of pilgrimage rituals. "For the Islamic community, the pilgrimage to the guardian tomb is believed to be a tradition. Pilgrimage is an Islamic rite that has taken root in Indonesian society. In conducting this pilgrimage, there are several motivations behind the spirituality behavior seeking this blessing. Sultan's pilgrimage can also be a medium to get kasekten and sacred. Exact power or magic is related to penetrating forces outside the human self. One of the goals of kesakten is to achieve personal goals, namely to gain power or maintain in order to survive from anyone's resistance. In general, there are several motivations that motivate these pilgrims to visit the tomb of Sultan Maulana Hasanudin or Muzawir. Here are some motivations (goals) of pilgrims who are respondents in this study. Some respondents stated that their goal of visiting the Tomb of Sultan Maulana Hasanudin or Muzawir was due to religious traditions. Several other informants stated that they made an arena pilgrimage wanting to know the Tomb of Sultan Maulana Hasanudin or Muzawir. Some pilgrims even came from outside Java. Other motivations include being in prayer, rejecting reinforcements, spiritual conduct